Energy transfer from Gd3+ to Sm3+ and luminescence characteristics of CaO–Gd2O3–SiO2–B2O3 scintillating glasses - Wantana N. (2017)
© 2016 Elsevier B.V. In this work, density, optical, photoluminescence and x-ray scintillation properties of calcium gadolinium silicoborate glass (CaO:Gd 2 O 3 :SiO 2 :B 2 O 3 ) have been investigated. Glasses were prepared by the conventional melt quenching technique. The results show that the density of glass increased with increasing of Sm 2 O 3 . The optical spectra of glass shows eleven discrete absorption bands at 360, 373, 403, 475, 944, 1077, 1225, 1368, 1468, 1520 and 1586 nm which are due to the transitions of 6 H 5/2 to 4 D 3/2 , 6 P 7/2 , 6 P 3/2 , 4 I 11/2 , 6 F 11/2 , 6 F 9/2 , 6 F 7/2 , 6 F 5/2 , 6 F 3/2 , 6 H 15/2 and 6 F 1/2 , respectively. The emission spectra were observed and assigned to 312, 563, 600, 646 and 703 nm by excitation at 275 nm. The emission intensity of Sm 3+ increased with increasing of Sm 2 O 3 concentration until 0.25 mol%, while decay time decrease with increasing of Sm 2 O 3 content. For results of the radioluminescence (RL), they perform four emission peaks with the strongest emission at 598 nm. Glass doped with 0.35 mol% Sm 2 O 3 show the highest RL emission. The integral scintillation efficiency of 0.35 mol% Sm 2 O 3 doped glass was determined as 25% of commercial BGO scintillator crystal.